The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1148/radiol.2442060837
|View full text |Cite
|
Sign up to set email alerts
|

CT Colonography in 546 Patients with Incomplete Colonoscopy1

Abstract: CT colonography has the potential to become an accepted technique for evaluation of the nonvisualized part of the colon after incomplete colonoscopy, and it can increase the diagnostic yield of masses and clinically important polyps in this part of the colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 31 publications
4
48
0
5
Order By: Relevance
“…Previous studies on CTC after incomplete colonoscopy have been conducted [6][7][8][9][10] . These studies were inhomogeneous regarding the patients' selection, because they included asymptomatic as well as symptomatic subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on CTC after incomplete colonoscopy have been conducted [6][7][8][9][10] . These studies were inhomogeneous regarding the patients' selection, because they included asymptomatic as well as symptomatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In order to complete evaluation of the colon, radiological examinations can be performed such as double contrast barium enema (DCBE) [5] and computed tomography colonography (CTC). In particular, several studies have shown that CTC is a valuable tool to evaluate the proximal colon after incomplete colonoscopy [6][7][8][9][10] , and the American Gastroenterologists Association (AGA) recognized that CTC is indicated for adults with failed colonoscopy [11] . We report the results of CTC systematically performed in subjects with positive FOBT and incomplete colonoscopy in the context of a population-based screening programme for CRC with FOBT.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively radiological imaging (e.g. CT colonography or barium enema) can be applied when endoscopy is technically not feasible or tumour stenosis does not allow complete colonoscopy [20,21]. In these cases colonoscopy should be performed 3-6 months after surgery.…”
Section: Tumour Diagnosis and Stagingmentioning
confidence: 99%
“…Several previous articles address large polyps and so-called masses, with this later group not clearly defined. Zalis et al [10] define them as lesions of 30 mm and larger, while Copel et al [11] and Kiraly et al [12] define them as lesions of 20 mm and larger. However, this is a conservative viewpoint with respect to the presence of malignancy (carcinoma) within the lesion and the chance of developing malignancy in the future (advanced adenoma).…”
mentioning
confidence: 99%